Green Economy dan Green Marketing: Studi Magnet Desa Penglipuran - Ni Kadek Inten Diana Sari; Ni Kadek Winda Yanti (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the influence of Green Economy, Green Marketing, and Green Brand Equity on tourists’ Visiting Intention toward Penglipuran Village, with Environmental Knowledge examined as a mediating variable. This study addresses the research gap by integrating sustainability-based constructs within a single structural model to understand how green practices shape tourists’ behavioral intentions. The study also aims to determine which sustainability dimension contributes most significantly to strengthening tourist intention in destinations recognized for their ecological and cultural preservation. Materials and methods. This study employed a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). A total of 190 respondents were selected through purposive sampling, consisting of tourists who had visited Penglipuran Village within the last year. Data were collected using Likert-scale questionnaires covering Green Economy, Green Marketing, Green Brand Equity, Environmental Knowledge, and Visiting Intention. Measurement model evaluation included tests of convergent validity, discriminant validity, and construct reliability, while structural model evaluation comprised R-Square, Q-Square, and path analysis using bootstrapping. Results. Findings showed that Green Economy has the strongest positive and significant effect on Visiting Intention, followed by Green Marketing, which demonstrated a moderate yet significant effect. Green Brand Equity indicated a positive but non-significant effect, while Environmental Knowledge showed no significant influence on Visiting Intention. Moreover, Environmental Knowledge did not mediate the relationships between the exogenous variables and Visiting Intention. The model explained 32% of the variance in Visiting Intention, indicating moderate explanatory power. Conclusions. The results highlight that tourists prioritize tangible sustainability practices—such as environmental management, cleanliness, cultural preservation, and green infrastructure—over cognitive factors such as environmental knowledge. Green Economy emerges as the most influential determinant in shaping visiting intention, suggesting that authentic and consistent implementation of green practices is essential for strengthening destination appeal. Environmental Knowledge does not function as a mediator, implying that experiential sustainability plays a more dominant role than cognitive awareness in influencing tourist behavior.